Prestasi Belajar IPS Siswa: Pengaruh Lingkungan Sekolah dan Motivasi Belajar - Sucipta, Komang Yoga Ari; Meitriana, Made Ary (Jurnal Pendidikan Ekonomi Undiksha, 2021)
This study aims to partially determine the effect of the school environment and learning motivation on social science learning achievement and to determine the simultaneous influence of the school environment and learning motivation on social science learning achievement. The type of research is causal. The population of this research  was all of the students of  grade VIII  SMP Negeri 2 Singaraja in the academic year 2019/2020. The sampling technique used was proportional random sampling and the number of samples were 77 students. The data collection techniques used were questionnaires, documentation and observation and data analysis of this research is  multiple linear regression analysis. The research results show that (1) the school environment has a significant effect on student achievement with a sig value of 0.016 < 0.05, (2) learning motivation has a significant effect on student achievement with a sig value of 0.015 < 0.05, (3) the school environment and learning motivation simultaneously significant effect on student achievement with sig. obtained is 0.015 <0.05.